A model reduction approach for hyperelastic materials based on Proper Orthogonal Decomposition. Issue 1 (21st October 2015) - Hürkamp, André; Kaliske, Michael
Abstract In this contribution, we present a model reduction approach for hyperelastic materials based on Proper Orthogonal Decomposition. A separation of the solution into time and space dependent functions is performed, which allows to compute reduced solutions within real time. The functionality of the method is demonstrated by a tensile test and is further applied to a stochastic analysis and a multi‐parametric analysis involving non‐linear material behaviour and large deformations. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)